That summer place - Barnett, Jill.; Macomber, Debbie; Wiggs, Susan (Don Mills, Ont. : MIRA Books, 2008)
"It's nothing special on the surface, merely a rambling old Victorian summerhouse on a secluded island, where the sky is blue and the water is clear. Yet after a month at the Rainshadow Lodge, people begin to change -- and fall in love. How else can you account for what happens to the most mismatched, unlikely couples? There's Beth, who's stuck sharing the lodge with a complete stranger -- and a difficult one at that. And Mitch, a workaholic on a deadline who has to depend on free-spirited Rosie, who functions on "island time." Not to mention Catherine, who's falling in love with Michael, the lodge's handyman -- for the second time!"--P. [4] of cover.
Old things / Jill Barnett -- Private paradise / Debbie Macomber -- Island time / Susan Wiggs.
Three novels, all previously published in 1998.
Keywords: Summer romance -- Fiction; Islands -- Fiction; Man-woman relationships -- Fiction; Love stories